Ethical Considerations in Adaptive Design Clinical Trials. (March 2017) - Laage, Thomas; Loewy, John W.; Menon, Sandeep; Miller, Eva R.; Pulkstenis, Erik; Kan-Dobrosky, Natalia; Coffey, Christopher
Adaptive design clinical trial methodologies offer both opportunities and challenges for observing basic ethical principles in human subject research. Using both published and unpublished adaptive design clinical trials, we have selected and reviewed examples of clinical trials with different design adaptations to discuss the ethical obstacles presented and often successfully resolved by these approaches, including (1) confirmatory trials for treatments widely accepted on the basis of uncontrolled case series or open-label trials (clinical equipoise and "justice" in the sense of which trial groups will "receive the benefits of research and bear its burdens") (infantile hemangioma/propranolol); (2) interim results analysis by unblinded data monitoring committees ("withholding information necessary to make a considered judgment" ["respect for persons"] versus compromising the trial's scientific basis) (BIG 1-98); (3) adaptations involving sample size reassessment or dose adjustment via dropping or adding treatment arms, allowing fewer subjects to produce statistically significant results, fewer subjects treated with ineffective/toxic doses, and more subjects given doses showing tolerance and treatment activity ("beneficence" or "protecting from harm and making efforts to secure wellbeing") (ECMO, Neuromyelitis Optica); (4) adaptive randomization inferential problems balanced against ethical benefits (trastuzumab vs taxane in advanced gastric cancer; ADVENT); (5) more efficient allocation of societal resources for research, in both public and commercial realms, versus uncertain regulatory acceptance (indicaterol; VALOR); and (6) platform, umbrella, and basket trials offering additional efficiencies (I-SPY II, BATTLE, Lung-MAP). The importance of careful design, meticulous planning, and rigorous ethical review of adaptive design trials on a case-by-case basis cannot be overemphasized.